Pluricentric Languages and Language Education Pedagogical Implications and Innovative Approaches to Language Teaching - Callies, Marcus; Hehner, Stefanie (Routledge Research in Language Education, 2023)
This book maps out the pedagogical implications of the global spread and diversification of pluricentric languages for language education and showcases new approaches that can take account of linguistic diversity. Moving the discussion of contemporary norms, aims, and approaches to pluricentric languages in language education beyond English, this book provides a multilingual, comparative perspective through case study examples of Spanish, French, German, Portuguese, Dutch, and Vietnamese. The chapters document, compare, and evaluate existing practices in the teaching of pluricentric languages, and highlights different pedagogical approaches that embrace their variability and diversity. Presenting approaches to overcome barriers to innovation in language education, the book will be of great interest to academics, researchers, doctoral students in the field of language education, as well as socio- and applied linguists. Practitioners interested in linguistic diversity more broadly will also find this book engaging.